EFL Instructors' Attitudes Toward Technology Integration in Islamic Boarding School Contexts: A Survey-Based Study on Selected Pesantren Modern - Aziz, Abdul (Journal of Linguistics, Literature, and Language Teaching (JLLLT), 2025)
This study investigates the attitudes of instructors teaching English as a Foreign Language (EFL) toward the integration of technology in the classroom. Drawing on data from 70 instructors working in modern Islamic boarding schools (pondok pesantren modern) across Jabodetabek and Banten during the 2024–2025 academic year, the study employs a descriptive survey design. It utilizes the Scale for Determining the Attitudes of Instructors Toward Technology in Teaching English as a Foreign Language, developed by ?pek and Kan (2019). The scale consists of three subdimensions—Avoidance, Willingness, and Adoption—and demonstrated strong reliability in the study (? = .83). Descriptive and inferential statistical analyses (t-tests and ANOVA) revealed that instructors generally exhibited low avoidance and high levels of willingness and adoption of technology in their pedagogical practices. No statistically significant differences were found based on gender, age, academic background, education level, teaching experience, or certification status. The findings highlight the critical need for continuous digital training and institutional support to sustain meaningful technology integration in EFL instruction, particularly within faith-based educational settings.